UPAYA UNITED NATIONS ASSISTANCE MISSION IN AFGHANISTAN (UNAMA) DALAM MEMPERJUANGKAN HAK PEREMPUAN DI AFGHANISTAN TAHUN 2021-2023 - Insan, Khairul; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study examines the efforts of the United Nations Assistance Mission in Afghanistan (UNAMA) to safeguard women’s rights in Afghanistan from 2021 to 2023, particularly after the Taliban’s return to power, which has curtailed women’s access to education, employment, health care, freedom of movement, and political participation. Employing a qualitative descriptive method that combines library research with an analysis of official UNAMA documents, UN reports, and relevant news sources, the study draws on pluralist perspectives, Clive Archer’s theory of international organizations, and Joshua S. Goldstein’s level‑of‑analysis framework. The findings show that UNAMA has successfully documented, reported, and advocated against abuses of women’s rights, including torture, restrictions on freedom of assembly, and discrimination within the judicial system. Despite advocacy through dialogue with the Taliban, reporting to the UN Security Council, and coordination with international actors for diplomatic pressure and humanitarian assistance, UNAMA faces significant challenges, such as limited enforcement authority and Taliban resistance to international norms. The research underscores the necessity of sustained and consistent international support to ensure the protection of women’s rights in Afghanistan. Keywords: Women's Rights, International Organizations, Pluralism, Taliban, UNAMA